Supercritical CO2 as a green solvent for the circular economy: Extraction of fatty acids from fruit pomace. Issue 41 (October 2020) - Campalani, Carlotta; Amadio, Emanuele; Zanini, Simone; Dall'Acqua, Stefano; Panozzo, Marina; Ferrari, Sara; De Nadai, Gabriele; Francescato, Stefano; Selva, Maurizio; Perosa, Alvise
Highlights: Fruit pomace of six different berries was extracted with scCO2 and hexane. Green extractions to obtain added value products from food industry waste. Fatty acids were extracted for the cosmetic industry. Selectivity towards fatty acids was higher with scCO2. The extraction yield was higher with hexane. Abstract: One of the empowering actions for the circular economy is deriving value from waste. In this context, recycling waste agro-food streams to make more sustainable chemical products through greener technologies promises to move away from the linear development model based on continuous growth and increasing resource throughput. We describe here the use of supercritical fluid extraction with carbon dioxide to extract fatty acids from waste pomace deriving from the preserves industry along with a comparison using hexane as solvent. The fatty acids extracted from the seeds and peels of raspberry, blueberry, wild strawberry, pomegranate, blackberry and blackcurrant using supercritical CO2 as a greener solvent were purer and richer in essential fatty acids than the hexane ones. The wild strawberry pomace extraction with supercritical CO2 is a representative example: selectivity towards fatty acids was 26 wt% ( vs. 1.4 % with hexane) and the extracts contained, 145.8 mg mL −1 polyunsaturated, 64.0 mg mL −1 monounsaturated and 46.8 mg mL −1 saturated fatty acids ( vs. 14.3 mg mL −1 total fatty acids with hexane).